A cleaner production of synthesis gas from glycerol using thermal water steam plasma. (1st September 2016) - Tamošiūnas, Andrius; Valatkevičius, Pranas; Grigaitienė, Viktorija; Valinčius, Vitas; Striūgas, Nerijus
Abstract: Glycerol, which is a by-product of biodiesel production, is considered to be a potential feedstock for synthesis gas generation. Therefore, the objective of this study was to investigate the use of thermal water steam plasma as one of the potential thermochemical technologies for cleaner production, to reform glycerol into the synthesis gas. A direct current plasma torch stabilized by a mixture of argon-steam vortex and operating at atmospheric pressure was used to produce active radicals. The reforming of glycerol was carried out at various flow rates of steam, glycerol, and plasma torch power. The modeling of chemical processes was also proposed. The reaction products were mostly gases with the concentrations as follows: hydrogen 47%, carbon monoxide 25.2%, carbon dioxide 12%, methane 5.4%, and acetylene 1.7%. The reforming system was quantified in terms of carbon conversion, hydrogen and carbon monoxide yield, and hydrogen/carbon monoxide ratio as well as energy efficiency and specific energy requirement. This study indicates that synthesis gas with a high content of hydrogen and carbon monoxide could be effectively produced from glycerol through the thermal water steam plasma reforming. Graphical abstract: Highlights: Glycerol reforming to synthesis gas using thermal steam plasma. The main reaction products are hydrogen and carbon monoxide. Active radicals accelerate reforming process. Process quantified in terms of energy efficiency.